Analisis Perbandingan Pengaruh Kualitas Audit, Likuiditas, Solvabilitas, Profitabilitas Terhadap Opini Audit Going Concern (Studi Perbankan Syariah Di Asia) - Ismawati Haribowo (STIE STEMBI Bandung Business School, 2013)
The purpose of study to test the effect of audit quality, likudity ratio, solvency, rentability and productivity This study used purposive sampling method. This sampling taken from 104 Islamic Banking in Soult Asia and Soulteast Asia from 2009-2012. Methods of data analysis descriptive analysis and analytical methods to test the research hypotheses using logistic regression analysis. The results of this study concluded that the liquidity ratio and the quick ratio is proxied by banking ratio has no effect on going concern audit opinion , while South Asia the other is a proxy for loan-to- deposit ratio (LDR) has an influence on the going concern audit opinion . The test results of the solvency ratio is proxied by using the ratio of primary , secondary risk assets ratio and risk ratio no effect on the going concern audit opinion . The test results of the profitability ratio is proxied by using the gross profit margin, net profit margin , return on equity (ROE ) , return on total assets (ROA) and return on the loan rate showed no influence on the going concern audit opinion.